Effects Differentiated Instruction on Student’ Retentive Knowledge in Chemical Bonding in Senior Secondary Schools in Federal Capital Territory, Abuja (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study investigated the effects of differentiated instruction on student’ retentive knowledge in Chemical Bonding in Senior Secondary Schools in Federal Capital Territory, Abuja. The study employed quasi experimental, pre-test, post-test experimental and control group design research designs. The population of the study was 6,309 SS II Chemistry students in senior secondary school two (SS II) in Kuje Area Council of the FCT. The study sample of the study was made up of 75 SSII chemistry students drawn from two public schools using simple random sampling technique by balloting. The study concluded that there was significant difference in the retentive ability of students taught chemical bonding using differentiated instruction. The study also indicated that that there was no significant difference in the retention mean scores of male and female students taught chemical bonding using differentiated instructional strategy. Based on the findings, the study recommends that Principals of government secondary schools in FCT should constantly organize workshops and sensitization programme to educate parents and guardians about the benefits of differentiated instruction and how they can support their children’s learning at home. Additionally, partnerships with local science organizations or universities can provide resources and opportunities for students to engage with chemistry in real-world contexts, enhancing their interest and retention of the subject matter. To aid smooth implementation of differentiated instruction in chemistry especially in chemical bonding, schools should encourage parental and community involvement in the educational process especially for the girl child.